Reinforced Magnetic-Responsive Electro-Ionic Artificial Muscles by 3D Laser-Induced Graphene Nano-Heterostructures - Xu, Zhenjin (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.